2014
DOI: 10.1155/2014/270213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recombinant Human Thyrotropin Administration on 24-Hour Arterial Pressure in Female Undergoing Evaluation for Differentiated Thyroid Cancer

Abstract: Objective. Thyroid-stimulating-hormone (TSH) receptors are expressed in endothelial cells. We investigated whether elevated TSH levels after acute recombinant TSH (rhTSH) administration may result in alterations in blood pressure (BP) in premenopausal women with well-differentiated thyroid carcinoma (DTC). Designs. Thirty euthyroid DTC female patients were evaluated by rhTSH stimulation test (mean age 40.4 ± 8.6 years). A 24 h ambulatory systolic and diastolic blood pressure (SBP, DBP) monitoring (24 hr ABPM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…The functional meaning of TSH outside the thyroid gland is not fully determined. It has been suggested that TSH may act as a modulator, operating at multiple different systems and organs (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Under clinical conditions similar to the ones applied in our study, rhTSH was shown to influence serum ghrelin levels (19), as well as serum levels of total cholesterol and triglycerides without any significant changes of high and low lipoproteins (20).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The functional meaning of TSH outside the thyroid gland is not fully determined. It has been suggested that TSH may act as a modulator, operating at multiple different systems and organs (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Under clinical conditions similar to the ones applied in our study, rhTSH was shown to influence serum ghrelin levels (19), as well as serum levels of total cholesterol and triglycerides without any significant changes of high and low lipoproteins (20).…”
Section: Discussionsupporting
confidence: 55%
“…Another study demonstrated that the serum level of platelet microparticles in athyroid patients rose fivefold after rhTSH stimulation (21). Exogenous rhTSH was also shown to have an impact on the cardiovascular system, where systolic and diastolic blood pressure increased 5 days after administration (22). What is more, rhTSH administration was associated with significant deterioration of renal perfusion and reduction in glomerular filtration (23).…”
Section: Discussionmentioning
confidence: 99%